Analysis of the Effectiveness of Pantene Bye #RAMBUTCAPEK Ads with the AISAS Method - Amartiwi, Yasinta; Tomy, Chairian (Journal of Business Administration and Strategy, 2025)
Advertising on Pantene shampoo uses Youtube social media as a promotional medium. The phenomenon that occurred, based on data on the number of viewers on Pantene Bye #RambutCapek advertisements, increased by 22,955,186 million in less than a month at the beginning of the yearِ 2022.ِ Thisِ researchِ is entitledِ "Analysis of the Effectiveness of Pantene Bye #RambutCapek Ads withِ theِ AISAS method"ِ byِ usingِ theِ Descriptiveِ Quantitativeِ method andِ takingِ samples in this study using nonprobability sampling methods with purposive sampling techniques. The sample taken amounted to 100 respondents who were calculated using the slovin formula. The results of the analysis of the AISAS method (Attention, Interest, Search, Action, Share) the effectiveness of Pantene youtube advertising with the results of the average Attention score of 90.8% which is categorized as Excellent, Interest of 74.4%, Search of 61.3%, Action of 61.6% with Good cartegory and Share of 58.4% which is categorized as average